Cationic Covalent Organic Framework with Ultralow HOMO Energy Used as Scaffolds for 5.2 V Solid Polycarbonate Electrolytes. Issue 21 (26th May 2022) - Liu, Jie; Zhang, Yuhao; Ji, Haoqing; Zhang, Jing; Zhou, Pinxin; Cao, Yufeng; Zhou, Jinqiu; Yan, Chenglin; Qian, Tao
Abstract: Solid polymer electrolytes (SPEs) have become promising candidate to replace common liquid electrolyte due to highly improved security. However, the practical use of SPEs is still restricted by their decomposition and breakage at the electrode interfacial layer especially at high voltage. Herein, a new cationic covalent organic framework (COF) is designed and synthesized as a reinforced skeleton to resist the constant oxidative decomposition of solid polycarbonate electrolyte, which can stabilize cathode electrolyte interphase layer to develop long‐term cycle solid lithium metal battery. The ultralow HOMO energy (−12.55 eV according to density functional theory (DFT) calculations), reflecting its oxidation resistance at positive potential, would be responsible for the high decomposition voltage of 5.2 V versus Li + /Li of solid polycarbonate electrolyte. Furthermore, the smooth surface of interfacial layer and inhibited decomposition reaction at cathode side is confirmed in solid LiCoO2 cell, which realizes high initial capacity up to 160.3 mAh g −1 at 0.1 C and greatly improved stability in 4.5 V class solid polymer lithium metal battery with high capacity retention over 200 cycles. This new type of high‐voltage resistant solid polymer electrolyte promotes the realization of high‐voltage cathode materials and higher energy density lithium metal battery. Abstract : A cationic covalent organic framework (COF) with strong antioxidant capacity is synthesized and used as high voltage resistant skeleton material in solid polycarbonate electrolyte. The stable COF acts as a reliable scaffold to prevent the collapse of cathode electrolyte interface (CEI) and the persistent decomposition of polycarbonate and the side reactions at electrode/electrolyte interface can be well restrained.